2018
DOI: 10.1136/jech-2017-210265
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations of active transport, employment status and objectively measured physical activity: analyses from the National Health and Nutrition Examination Survey

Abstract: Findings from the present study support interventions to promote active transport to increase population level physical activity. Additional strategies are likely required to promote physical activity among unemployed women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…First, a different method was used to assess outcomes. PA was evaluated using a self-report questionnaire in previous studies [ 15 , 16 , 22 ], whereas we measured PA using a triaxial accelerometer. The result of the relationship between disease activity and PA might have been different because self-reported PA and the more accurate accelerometer-measured PA results are different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a different method was used to assess outcomes. PA was evaluated using a self-report questionnaire in previous studies [ 15 , 16 , 22 ], whereas we measured PA using a triaxial accelerometer. The result of the relationship between disease activity and PA might have been different because self-reported PA and the more accurate accelerometer-measured PA results are different.…”
Section: Discussionmentioning
confidence: 99%
“…The triaxial accelerometer can evaluate changes in activity levels and separate sedentary time and active time [ 19 21 ]. Population-based research, such as the National Health and Nutrition Examination Survey, have used accelerometers for PA measurements rather than conventional methods [ 22 ]. By contrast, some studies examining the relationship between RA disease activity and PA levels indicated a correlation between decreased disease activity and increased PA based on a self-reported questionnaire [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, a different method was used to assess outcomes. PA was evaluated using a self-report questionnaire in previous studies, (3,4,10) whereas we measured PA using a triaxial accelerometer. The result of the relationship between disease activity and PA might have been different because self-reported PA and the more accurate accelerometer-measured PA results are different.…”
Section: Discussionmentioning
confidence: 99%
“…(7)(8)(9) Population-based research, such as the National Health and Nutrition Examination Survey, have used accelerometers for PA measurements rather than conventional methods. (10) Evaluating PA and rehabilitation in RA patients can help prevent heart diseases, diabetes, hypertension, depression, and osteoporosis and are associated with an improved low mortality rate. (11)(12)(13) In several studies evaluating moderate-to-vigorous PA (MVPA) using accelerometers in patients with RA, RA patients showed lower MVPA than healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity currently accounts for nearly 10% of the main non-communicable chronic diseases worldwide 1 . This is partly due to the increase in individuals' involvement in activities requiring less energy expenditure, such as watching TV and sitting in the workplace for long periods of time 2,3 or during transport 4 . One of the strategies used to reduce physical inactivity has been the creation and maintenance of public open spaces such as squares and public parks 5,6 .…”
Section: Introductionmentioning
confidence: 99%